Arthroscopically Assisted Cannulated Screw Fixation for Treating Type III Tibial Intercondylar Eminence Fractures: A Short-Term Retrospective Controlled Study - Zheng, Chao; Han, Huanli; Cao, Yujiang (Frontiers in Surgery, 2021)
Background: This study presents the clinical results from 22 children who underwent minimally invasive arthroscopically assisted screw fixation for the treatment of intercondylar eminence fractures. Methods: We retrospectively analyzed the clinical data of 22 children (aged 7.5 to 13.5 years) with type III tibial intercondylar eminence fractures who were treated in our department from March 2007 to September 2019. According to the type of operation, the patients were divided into two groups: group A (n=12) received arthroscopically assisted cannulated screw fixation, and group B (n=10) received open reduction and cannulated screw internal fixation. Radiography scans, Lysholm scores, International Knee Documentation Committee (IKDC) 2000 subjective scores, Tegner scores, range of motion (ROM) of the knee, the anterior drawer test (ADT), the Lachman test, and the pivot-shift test were used to evaluate the clinical efficacy. Results: All 22 children were evaluated over a 12- to 58-month follow-up period (mean: 27.5 months). At the final exam, group A was significantly superior to group B in Lysholm scores (93.33±3.55 VS 86.20±4.52), IKDC scores (92.06±3.55 VS 86.07±5.81), and Tegner scores (7.75±0.87 VS 6.40±0.52) and presented shorter operative times (25.42±3.97 VS 35.00±5.27). The differences were statistically significant (P<0.05). All the incisions healed primarily. No complications, such as fracture fragment displacement, delayed epiphyseal growth, or knee joint dysfunction, were observed. The drawer test, Lachman test, and pivot-shift test were negative for all patients. Conclusions: Arthroscopically assisted cannulated screw fixation is effective and safe for the treatment of tibial intercondylar eminence fractures, providing excellent stability and quick recovery of joint function.